2020
DOI: 10.1002/ece3.6029
|View full text |Cite
|
Sign up to set email alerts
|

Whistle variation in Mediterranean common bottlenose dolphin: The role of geographical, anthropogenic, social, and behavioral factors

Abstract: The studies on the variation of acoustic communication in different species have provided insight that genetics, geographic isolation, and adaptation to ecological and social conditions play important roles in the variability of acoustic signals. The dolphin whistles are communication signals that can vary significantly among and within populations. Although it is known that they are influenced by different environmental and social variables, the factors influencing the variation between populations have recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 110 publications
(216 reference statements)
1
24
0
Order By: Relevance
“…Previous studies have associated whistle duration with context and group size (Janik et al, 1994;Wang et al, 1995;Morisaka et al, 2005b). For example, in Croatia and Sardinia bottlenose dolphins increased whistle duration with increasing group size regardless of boat traffic (La Manna et al, 2020). Unfortunately, we do not have data on the number of dolphins present at Dolphin Bay during the lockdown.…”
Section: Measurementioning
confidence: 79%
“…Previous studies have associated whistle duration with context and group size (Janik et al, 1994;Wang et al, 1995;Morisaka et al, 2005b). For example, in Croatia and Sardinia bottlenose dolphins increased whistle duration with increasing group size regardless of boat traffic (La Manna et al, 2020). Unfortunately, we do not have data on the number of dolphins present at Dolphin Bay during the lockdown.…”
Section: Measurementioning
confidence: 79%
“…The detection of whistles, in particular, could be expected since they are known to play a fundamental role in bottlenose dolphins’ intraspecific communication and social activity [ 49 , 50 ]. However, only a couple of studies have characterized whistles emitted in epimeletic contexts, and they reported high emission rates [ 9 , 17 ], and increased duration and number of inflection points [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed bottlenose dolphins are known to change the acoustic parameters of their whistles depending on the contexts [ 51 ] and these variations could potentially act as stress indicators [ 16 ]. In the first event, a majority of modulated whistles (11/12 OWs) were recorded, that differed in duration and frequency parameters from the mean values observed in the Mediterranean sea [ 50 , 52 ]. All frequency parameters were higher in the present study with respect to the mean Mediterranean values, while duration and number of inflection points were slightly lower.…”
Section: Discussionmentioning
confidence: 99%
“…The dolphin habitat in the oceans is totally different, and individuals within groups are often dispersed over wide distances. They communicate in the form of whistles that transmit efficiently under water and differ in character chiefly by geographic distance and local environmental factors (La Manna et al , 2020). This study analyzed whistle variation in two geographically separate groups of the Mediterranean common bottlenose dolphin ( Tursiops truncatus ), one around Sardinia and the other near Croatia on the opposite side of the Italian peninsula.…”
Section: Many Animal Species “Speak” Dialectsmentioning
confidence: 99%